Design Principles of a Physical Protection System for Data Centres: Essential Requirements for the Security Staff in the Physical Protection System - Horváth, Tamás (Magyar Rendészet, 2020)
The best practices and knowledge of different guidelines would be absolutely useful for professionals in the field of security technology. It is essential for the design and implementation of the data centres which are not really common facilities due to security reasons. Their location, proper activities, even the circumstances of their operation, all this should not be public knowledge. The design and implementation of the data centres depend on their security risk level. This may be fairly known for professionals, but a summary of the essential requirements would be useful for all people involved. In my practice, our company has got a chance to make a complex security plan for a Data Centre, so I would like to present the architectural and security aspects which may be important in the given case. Since a certain level of security is required in a given case, and different levels belong to different physical protection systems (PPS), I have created a facility security matrix to serve as a guideline and to help to decide what kind of PPS should be installed in different cases.